Numerical treatment of time dependent magnetohydrodynamic nanofluid flow of mass and heat transport subject to chemical reaction and heat source - Yun-Xiang Li (Elsevier, 2022)
The thermophysical properties of the nanofluids override the physical properties of conventional fluids due to the high thermal conductivity of the nanoparticles. The applications of nanofluids have varied use in the era of bio-engineering and thermal sciences. Moreover, the nanoparticles attributed the significances in human blood arteries. Therefore, the present analysis manifests with the free convection of electrically conducting nanofluid embedding with resistive forces such that the magnetic field and permeability of the medium. The augmentation in the heat transfer properties is obtained because of the inclusion of radiative heat energy and absorption diffusion. Moreover, the nanoparticles volume fraction is focused with implementation of chemical reaction. Numerical treatment using the code in-build MATLAB code pdepeis employed for the transformed unsteady flow problem. The graphical computations against flow parameters are worked with justified physical importance. A declining change in nanoparticles is examined due to Prandtl number which is more progressive for steady case. The decreasing change in velocity is more dominant for nanoparticles as compared to pure fluid. The nanoparticles concentration reduces for effective variation of chemical reaction constant and Lewis number.